GOODS DELIVERY SYSTEM IN PT.LAJU MERAPI - Siti Aminah (Jurnal Sistem Informasi, 2007)
The development of increasingly sophisticated computer very helpful in data processing still using manual systems. This is often a problem associated with the accuracy of the data that caused delays in data processing. The information is valuable information quickly and accurately. Then needed a computerized system as supporters. System delivery service designed with the aim to facilitate the processing of data and preparing reports.